PENGARUH KUALITAS PRODUK DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA BUSSINES CENTER SMK YAPIA PARUNG DI KABUPATEN BOGOR - Silvia; Rini Dianti Fauzi (Jurnal Riset Multidisiplin Edukasi, 2025)
This research aims to determine whether there is an influence on product quality and service quality on purchasing decisions at the Yapia Parung Vocational School Business Center in Bogor Regency, either partially or simultaneously. The population in this study were teachers, staff and also students of Yapia Parung Vocational School in Bogor Regency, totaling 1,060 students in 2021. The method used is an associative quantitative research method. Determining the number of samples used was using a probability sampling technique using the Slovin 5% formula, namely 92 people. There are several analytical methods used in this research, namely descriptive statistical analysis, validity test, reliability test, classical assumption test, statistical test, correlation coefficient test, and hypothesis test with the help of SPSS 25 software. Based on the results of the hypothesis test, it was found that product quality had a significant effect. on purchasing decisions at the Yapia Parung Vocational School Bussines Center in Bogor Regency with a value of tcount>ttable or (14.620>1.987) with a significance value of 0.00 <0.05, it can be concluded that partially product quality has a significant effect on purchasing decisions at Businesses Yapia Parung Vocational School Center in Bogor Regency. Based on the results of the service quality hypothesis test on purchasing decisions tcount > ttable or (17.657 > 1.987) with a significance value of 0.00 < 0.05, it can be concluded that partially service quality has a significant effect on purchasing decisions. Based on the results of the hypothesis test, the value Fcount>Ftable or (169.554 > 4.504) was obtained with a significance value of 0.00 <0.05, so it can be concluded that simultaneously product quality and service quality together have a significant influence on purchasing decisions at the Business Center. Yapia Parung Vocational School in Bogor Regency.